A Retrospective Comparative Study of Clinicopathological Features in High-Grade and Low-Grade Serous Ovarian Carcinoma - Ham, Jonathan; Nasser, Andi S.H.D.; Masadah, Rina; Rauf, Syahrul; Nelwan, Berti J.; Miskad, Upik A; Cangara, Muhammad H; Tawali, Suryani (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Backgroud: Ovarian carcinoma is the third most common malignancy in Indonesian women after breast and cervical cancer. Serous ovarian carcinoma is the most frequent subtype, divided into low-grade and high-grade types, each with distinct genetic and biological characteristics. Objective:This study aims to compare the clinicopathological features of high-grade and low-grade serous ovarian carcinoma. Methods: A retrospective cross-sectional study was conducted using 77 paraffin-embedded samples of serous ovarian carcinoma. Clinical and pathological data including age, body mass index (BMI), age at menarche, and parity were collected and analyzed using the chi-square test. Results: Patients aged >50 years accounted for most cases, with 64.3% presenting high-grade serous carcinoma (HGSC). Overweight/obesity was observed in 40.3% of cases. Early menarche (<13 years) was reported in 78%, and 42.7% were multiparous. No significant differences were found in clinical variables between HGSC and low-grade serous carcinoma (LGSC). Histopathologically, HGSC showed more pronounced cytologic atypia, necrosis, and metastasis. Conclusion: High-grade serous carcinoma demonstrates greater aggressiveness compared to its low-grade counterpart. Histopathological assessment plays a critical role in diagnosis, treatment decisions, and prognosis evaluation.